Implementasi PADUKO (Pelayanan Dokumen Kependudukan Online) Pada Dinas Kependudukan dan Pencatatan Sipil (Disdukcapil) Kota Padang Panjang - Naziva Amanda Putri; Aidinil Zetra; Roni Ekha Putera (JDKP Jurnal Desentralisasi dan Kebijakan Publik, 2022)
This study found facts that contradict the issue of the importance of good implementation in a public policy, in the technology-based public policy program in the City of Padang Panjang PADUKO (Population Document Service Online), programs that can streamline community time and energy do not run properly in the City. Long Field. The purpose of this study is to see how the implementation of the PADUKO Policy at the Department of Population and Civil Registration of Padang Panjang City. This study was analyzed using the Merilee S. Grindle policy implementation theory which consists of two indicators, namely the content of the policy (context of policy) and the policy environment (content of policy). This research uses descriptive research method with a qualitative approach. Based on the results of research with Merilee S. Grindle theoretical analysis, it can be said that the application of PADUKO at the Department of Population and Civil Registration of Padang Panjang City is not good enough. There are several obstacles to the PADUKO policy, namely, inadequate human resources and a heavy workload, inadequate infrastructure, socialization strategies carried out by implementors are ineffective and not well targeted